Selection of ionic liquids and deep eutectic solvents via quantum chemical methods and liquid-liquid equilibria involved in the extractive denitrogenation of diesel / Hanee Farzana Hizaddin - Hanee Farzana, Hizaddin (2016)

(untitled)
The removal of nitrogen compounds from transportation fuel is proven to enhance the efficiency of desulfurization process, which aims to meet the rigorous regulations regarding zero-emissions. Ionic liquids (ILs) and deep eutectic solvents (DESs) were screened for this purpose using quantum chemical methods. Geometry optimization was performed for all involved species at Hartree-Fock level and 6-31G* basis set. Generation of cosmo files using Density Functional Theory and Triple zeta valence potential basis set was carried out at single point calculation. The cosmo files were used to obtain σ-profiles and σ-potentials for qualitative screening of ILs and DESs. (i) The screening of ILs revealed that cations with an aromatic ring have better capacity as hydrogen bond donors (HBDs) than do non-aromatic cations, whereas the acetate anion appeared to have better affinity towards HBD than did ethylsulfate and methanesulfonate anions. The σ-profile and σ-potential analysis confirmed that there is an interaction between nitrogen compounds and cations via CH-π interaction along with between nitrogen compounds and anions via hydrogen bonding. Moreover, a detailed quantum chemical calculation was performed to investigate the interaction between ILs and nitrogen compounds at molecular level, in which optimized geometry was used to obtain the orbital energies, global scalar properties, interaction energies and partial charges. The calculations indicated that cations with an aromatic ring, that is, imidazolium and pyridinium, combined with either ethylsulfate or methanesulfonate anion have favorable interaction with nitrogen compounds in comparison to cations without an aromatic ring. (ii) The screening of DESs showed that the interaction between nitrogen compounds and DESs is based on hydrogen bonding. Altogether, 94 DESs were examined quantitatively by predicting the values of the activity coefficients at infinite dilution of nitrogen compounds and diesel in the DESs. These were then used to estimate selectivity, capacity and iv performance index at infinite dilution as the basis of the screening process taking into account the cation, anion and HBD choices as well as the salt:HBD molar ratio. Based on the screening results, 22 ternary liquid-liquid equilibria (LLE) experiments were carried out at room temperature and atmospheric pressure to test three ILs – namely 1-ethyl-3-methylimidazolium ethylsulfate, 1-ethyl-3-methylpyridinium ethylsulfate, and 1-ethyl-3-methylimidazolium methanesulfonate, and two DESs – namely tetrabutylammonium bromide/ethylene glycol (1:2) and tetrabutylphosphonium bromide/ethylene glycol (1:2). The aim was to remove non-basic and basic nitrogen compounds from n-hexadecane as a model diesel compound. NMR spectroscopy was used for the compositional analysis. Consistency tests were performed to ascertain the reliability of all experimental data. All ternary systems reported distribution ratios and selectivity values greater than unity with minimal cross-contamination between the extract and raffinate phases. The ternary LLE data were correlated with NRTL model and compared with COSMO-RS predictions, both of which were in excellent agreement with the experimental tie-lines. In conclusion, the quantum chemical screening of ILs and DESs explained the interaction between ILs/DESs and nitrogen compounds at molecular level, which facilitates solvent selection for the denitrogenation process. The ternary LLE experiments with the selected ILs and DESs confirmed that these solvents have high potential for industrial extractive denitrogenation.